Teacher identity continuum: A framework for teacher identity shifts online - El-Soussi, Amira (2024)
In March 2020, due to COVID-19, English faculty in higher education institutions (HEI) in the United Arab Emirates (UAE) had to migrate to and administer online courses despite limited familiarity and training in online delivery. Moving online, teachers had to negotiate their long-held beliefs, teaching practices and roles as they navigated a new educational context, thus further reinterpreting their professional identities. In the face of change, teachers may experience a sense of insecurity that influences their identity development, and research is still early in understanding teacher identity formation, factors impacting identity changes, and the role of identities in teachers’ motivation and learning (Schutz et al., 2018). Therefore, this research draws on identity theory to examine how 14 English faculty members in HEIs in the UAE negotiated their beliefs, roles, and practices as they shifted online due to the pandemic. Through a qualitative exploratory multimethod approach, including mind maps and semi-structured interviews, and thematic analysis, my findings led to the development of a new framework instrumental in understanding the reshaping of teacher identities through the forced transition from FTF to online teaching. My research positioned teachers’ online identities on a Teacher Identity Continuum (TIC) with Digital Adapters, Digital Resisters, and Digital Ambivalents, including a spectrum of related beliefs, roles and practices. This framework has several practical implications for teachers, teacher education, and institutional leadership as they manage transitions and times of change.